Assessment of drug permeability using a small airway microphysiological system - Geiger, Robert M.; Rahman, Shekh M.; Rashid Roni, Md Shadiqur; Sullenberger, Catherine; Mistry, Sabyasachy; Shea, Katherine; Tariq, Isra; Ismaiel, Omnia A.; Matta, Murali K.; Hyland, Paula L.; Berdichevski, Sasha; Ribeiro, Alexandre J. S.; et al. (Frontiers in Pharmacology, 2025)
BackgroundThere is a need to reliably predict the permeability of inhaled compounds during the development of new and generic drugs. A small airway microphysiological system (MPS) that can recapitulate the pulmonary air-liquid interface (ALI) with primary epithelial and vascular endothelial cell layers may provide a more physiologically relevant environment for measuring drug permeability than simpler two-dimensional in vitro cell culture platforms. Therefore, we evaluated the use of a small airway MPS to measure the permeability of inhaled drugs.MethodologyPrimary human lung epithelial cells were seeded onto the top channel of the chip and cultured for 14 days at ALI to promote monolayer differentiation, followed by addition of endothelial cells into the bottom channel. Due to the non-specific binding properties of polydimethylsiloxane (PDMS), a drug absorption study was conducted to quantify non-specific binding to the material. Drug permeability was evaluated by passing each compound (10 µM) through the top channel and measuring the amount of drug that permeated into the bottom channel over the time course of 30, 60, 120, and 180 min.ResultsConfocal micrographs demonstrated the presence of tight junctions along with basal, goblet, and ciliated cells in the top channel and attachment of endothelial cells in the bottom channel. Insignificant nonspecific binding to the MPS was observed with albuterol sulfate, formoterol fumarate, and olodaterol hydrochloride (HCl), while fluticasone furoate showed significant nonspecific binding as only 6%–44% of the drug was recovered at 30 and 120 min, respectively. As a result, fluticasone furoate was excluded from further analysis. Permeability studies estimated an apparent permeability (Papp) of 1.02 × 10−6 cm/s for albuterol sulfate, 0.0813 × 10−6 cm/s for olodaterol HCl, and 2.44 × 10−6 cm/s for formoterol fumarate.DiscussionTaken together, the small airway MPS recapitulated relevant cell types and many morphological features in the lung. The apparent permeabilities measured indicated that albuterol sulfate and formoterol fumarate would be categorized as highly permeable, while olodaterol HCl would be categorized as a low permeable drug.